Determination of the Hydration Damage Instability Period in a Shale Borehole Wall and Its Application to a Fuling Shale Gas Reservoir in China. (2nd June 2019) - She, Haicheng; Hu, Zaiqiang; Qu, Zhan; Zhang, Yao; Guo, Hu
Abstract : In reviewing Chinese shale gas reserves and national policies regarding shale gas exploitation, shale gas will be of critical importance in providing clean natural gas to China. However, compared to those in the United States, the cost of shale gas extraction and the complex problems encountered in more complex and deep drilling in China are key technologies that need to be overcome. Shale wellbore wall instability is a complex problem that often occurs during drilling. During the process of drilling in shale, the complex stress and fluid-structure interactions result in the wall rock generating a strong hydration diffusion and swelling effect, which alters the stress distribution in the rock wall and deteriorates the mechanical parameters of the rock. This results in instability damage of the shale wellbore wall. In this study, the stratigraphic stress characteristics of the Fuling Shale Gas Field were initially predicted, and the shale sample phase composition and development of bedding and microcracks were analyzed using X-ray diffraction and scanning electronic microscopy. The main driving potential difference function between the drilling fluid and shale was analyzed, and a radial adsorption diffusion model of the shale plane was established. Through a laboratory study, the space time change law of the water diffusion of the shale rock was assessed as well as the rock damage evolutionary law of the elastic modulus and compressive strength with water content. Then, combined with the shale hydration stress and strength deformation theory, a damage evolutionary equation for shale with water was derived, and the shale damage evolutionary limit equation and the method of determining the collapse cycle were established. Finally, the method was applied to the Fuling Shale Gas Field, the largest shale gas field in China, and a shale wellbore collapse cycle of approximately seven days in the field was obtained. The severity of economic loss resulting from wellbore wall instability was also determined. This study provides insight and guidance for reducing the costs of shale gas reservoir well drilling and efficient development.